Pendampingan Penguatan Manajemen Bisnis UMKM Koja Di Kabupaten Indramayu - Yudianto, Agus; Supriatna Sonjaya , Nana; Nurhayati, Nunung (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
UMKM Koja IM is a home industry that is active in the processing and selling of various crackers. The aim of course is to make the marketing process more effective and efficient. By making direct observations and conducting interviews. assisting in the production process, marketing, and financial reports. During this service, partners still experienced difficulties in production because all the equipment was still manual. We hope that this activity does not stop here but can be sustainable so that it can still help MSMEs in the region